Differences in emotion regulation difficulties among adults and adolescents across eating disorder diagnoses. Issue 10 (13th May 2018) - Anderson, Leslie K.; Claudat, Kimberly; Cusack, Anne; Brown, Tiffany A.; Trim, Julie; Rockwell, Roxanne; Nakamura, Tiffany; Gomez, Lauren; Kaye, Walter H.
Abstract: Objective: Although much empirical attention has been devoted to emotion regulation (ER) in individuals with eating disorders, little is known about ER across a wide age range and among different ED subtypes. The current study sought to examine ER in a sample of eating disorder patients. Method: A total of 364 adults and adolescents with anorexia nervosa restricting subtype (AN‐R), anorexia nervosa binge/purge subtype (AN‐BP), or bulimia nervosa (BN) were assessed with the Difficulties in Emotion Regulation Scale (DERS). Results: Older ages were associated with higher DERS total, nonacceptance, goals, and impulsivity scores. When controlling for age, patients with BN and AN‐BP had higher overall DERS scores than those with AN, and there were some differences among diagnostic subtypes on specific facets of ER. Conclusions: These results indicate that treatments for emotion dysregulation may be applied across eating disorder diagnoses and ages, and inform how these strategies apply to different diagnostic groups.